(untitled) (KONFERENSIYA, 2025)
This article examines the evolving landscape of anti-doping practices in modern sports. As performance enhancement technologies advance and the stakes of international competitions rise, sport organizations face growing challenges in ensuring clean, fair, and ethical athletic performance. The study explores how anti-doping strategies have transformed—from traditional urine testing to cutting-edge genetic analysis, biological passports, intelligence-based investigations, and global harmonization under the World Anti-Doping Agency (WADA). Findings indicate that anti-doping today is no longer limited to laboratory detection; it involves cooperation between governments, sport bodies, laboratories, and law-enforcement agencies. Despite progress, ongoing threats such as gene doping, micro-dosing, and state-organized doping schemes require further innovation and stronger governance